Modified Green-Ampt model for infiltration analysis in loess area and its parameter determination and verification - Yunxin Zheng; Zhiping Hu; Rui Wang; Songli Chen; Xiang Ren; Yonghui Zhang (Scientific Reports)
Abstract Water infiltration into soil is important in geotechnical engineering. The classical Green-Ampt (GA) infiltration model is widely used in soil infiltration due to its physical significance, but it ignores the actual unsaturated layer in the infiltration process and has some deficiencies. Thus, the present study established a modified GA infiltration model (MLGA model) using Darcy’s infiltration law and continuity equation to fully consider the variation characteristics of the soil water profile in the infiltration process. The Philip model and the GA model have the same physical basis. By combining the internal relationship between the infiltration rate and cumulative infiltration of the two models, the expression of matrix suction of the MLGA model was obtained. The existing measured data was used to verify the correctness and applicability of the MLGA model. Finally, the sensitivity analysis of the critical parameters of the model was performed. The results showed that the MLGA model is reliable and can be used for water infiltration analysis in loess sites. When the MLGA model is used to calculate the infiltration depth, the maximum relative error between the calculated value and the measured data is less than 10%, and the average relative error is 5.54%, which indicates that the model has a high calculation accuracy. The average error of the MLGA model is 24.47% of the Kostiakov model and 80.42% of the existing modified GA model (LGAM model). Sensitivity analysis of the saturated permeability coefficient, initial water content, saturated water content, and matrix suction was performed using the single-factor disturbance method. The influence of each parameter on infiltration depth was summarized, and the sensitivity of each parameter was quantitatively evaluated, which revealed that saturated water content is a highly sensitive parameter. When using the MLGA model to calculate infiltration depth, the accuracy of saturated water content should be ensured first. Finally, the difference between the MLGA model and the LGAM model in describing the whole process of water infiltration is discussed, and the influence mechanism of critical parameters on the water infiltration process is deeply analyzed. The established MLGA model provides theoretical support for further study of the loess water infiltration mechanism.